Renal tubular injury during cardiopulmonary bypass as assessed by urinary release of N‐acetyl‐ß‐D‐glucosaminidase. Issue 9 (26th July 2017) - Lannemyr, L.; Lundin, E.; Reinsfelt, B.; Bragadottir, G.; Redfors, B.; Oras, J.; Ricksten, S.‐E.
Abstract : Background: Acute kidney injury (AKI) is a common complication with a major impact on morbidity and mortality after cardiac surgery with cardiopulmonary bypass (CPB). The aim of the present study was to perform a detailed analysis on the release of the tubular injury biomarker N‐acetyl‐b‐D‐glucosaminidase (NAG) during and early after CPB and to describe independent predictors of maximal tubular injury. We hypothesized that renal tubular injury occurs early after the onset of CPB. Methods: In this prospective observational study, we included 61 patients undergoing open cardiac surgery with an expected CPB duration exceeding 60 min. The urinary NAG levels were measured at 30 min intervals during CPB, as well as early (30 min) after CPB and post‐operatively. Independent predictors of tubular injury were identified using an Interquantile multivariate regression model. Results: Already 30 min after the onset of CPB, NAG excretion was significantly increased ( P < 0.001), followed by a sixfold peak increase after discontinuation of CPB ( P < 0.001). In the multivariable regression model, CPB duration ( P < 0.05) and the degree of rewarming during CPB ( P < 0.05), were independent predictors of peak NAG excretion. Conclusion: In cardiac surgery, a renal tubular cell injury is seen early after onset of CPB with a peak biomarker increase early after end of CPB. The magnitude of this tubular injury is independently related to CPB duration and the degree of rewarming. Efforts made to decrease the CPB duration and to avoid hypothermia and the need for rewarming may decrease the risk for tubular injury.